(untitled) (American Journal of Islam and Society, 2015)
Over the past few years, an increasing number of academic publications have focused on the life and work of the Sufi master and theologian Abū l-Qāsim ‘Abd al-Karīm b. Hawāzim al-Qushayrī (d. 465/1072 in Nishapur). While this increased interest has filled in many gaps in our understanding of this man, an important figure for the Islamic mystical tradition, Nguyen’s monograph represents the first in-depth inquiry into Qushayrī and his doctrine. Nguyen’s book, developed from his doctoral dissertation, concentrates on the Laṭā’if al-Ishārāt (hereafter LI), typically considered a mystical exegetical treatise but which Nguyen shows should be seen in a broader and more nuanced light. He analyzes the text through the concept of “tradition,” reading it as the result of a network of different cultural and spiritual influences. Their unification in this exegetical treatise can be considered Qushayrī’s main achievement. As such, Nguyen’s work represents a major contribution in the fields of Qur’anic and Sufi studies as well as the broader field of medieval intellectual history. The book’s nine chapters cover the following subjects: In the introduction the author positions the LI vis-à-vis the different exegetical traditions (juridical, encyclopedic, and theological), arguing that it belongs to what Walid A. Saleh calls the “Nishapuri school” of exegesis. Thus, as Nguyen points out, Qushayrī’s Tafsīr is “located and contextualized onto a number of different but overlapping historical axes” (p. 16) ...